The impact of genomics on population genetics of parasitic diseases. (February 2015) - Hupalo, Daniel N; Bradic, Martina; Carlton, Jane M
Highlights: We summarize the influence of genomics on parasite population genetics. The explosion of genomic data has enabled new types of investigations. Population genomic data has refined estimates of LD and heterozygosity in parasites. Plasmodium population genomics is a foundation for studies of neglected parasites. Abstract : Parasites, defined as eukaryotic microbes and parasitic worms that cause global diseases of human and veterinary importance, span many lineages in the eukaryotic Tree of Life. Historically challenging to study due to their complicated life-cycles and association with impoverished settings, their inherent complexities are now being elucidated by genome sequencing. Over the course of the last decade, projects in large sequencing centers, and increasingly frequently in individual research labs, have sequenced dozens of parasite reference genomes and field isolates from patient populations. This 'tsunami' of genomic data is answering questions about parasite genetic diversity, signatures of evolution orchestrated through anti-parasitic drug and host immune pressure, and the characteristics of populations. This brief review focuses on the state of the art of parasitic protist genomics, how the peculiar genomes of parasites are driving creative methods for their sequencing, and the impact that next-generation sequencing is having on our understanding of parasite population genomics and control of the diseases they cause.